Extreme Climate Index Projection using the Shared Socioeconomic Pathways Model (SSP 5-8.5) in Jambi Province 2026-2100 - Riza, Moch Nurul; Saad, Asmadi; Zuhdi, Mohd (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Global climate change has caused an increase in the frequency and intensity of extreme rain events, including in Jambi Province which is vulnerable due to geographical conditions, land use intensity and the dominance of the plantation sector. Extreme rain events have the potential to cause flooding, damage infrastructure and disrupt food security, resulting in future climate projections to support mitigation and adaptation efforts. . Objective: The aim of the research is to project changes in extreme climate indices and analyze their spatial distribution patterns and impacts. Methods: The data used includes observed rainfall from 41 BMKG rain posts, CHIRPS reanalysis data, and CMIP6 model data for historical and projection periods. Results and Discussion: The research results show that most extreme rainfall indices have increased until the end of the 21st century. Intensity indices such as PRCPTot, RX1day, RX5day, R95p, and R99p show a significant upward trend, indicating an increase in very heavy rain events. Conclusion: Spatially, the central region is the area most vulnerable to increased rainfall extremes.